Temperature-Sensitive Mutations in Drosophila Melanogaster, IV. A Mutation Affecting Eye Facet Arrangement in a Polarized Manner - Foster, Geoffrey G. (1970)
Drosophila melanogaster females heterozygous for the mutation N(60g11) have wild type eyes when raised at 29°C but a disrupted arrangement of facets and extra bristles at 21°C. Shifts of cultures from one temperature to the other at different stages in development revealed that facet arrangement is altered by temperature during the third larval instar. The facet pattern is affected in a vertical wave that proceeds anteriorly from the posterior rim of the eye. The role of the Notch locus in development is briefly discussed.